122k views
5 votes
PLEASE HELP ASAP simplify the expressions below

1) 8 + (x-4 )2

2) - (x+3) + 3(-x -6)

3) 2(x -y +z) -4(x -y +z)

User VGR
by
5.2k points

2 Answers

1 vote

1) 8 + (x-4 )^2

= 8 + x^2 -8x + 16

= x^2 - 8x + 24

2) - (x+3) + 3(-x -6)

= -x - 3 -3x - 18

= -4x - 21

3) 2(x -y +z) -4(x -y +z)

= (x -y +z) (2 - 4)

= (x -y +z)(-2)

= -2x + 2y -2z

User Srinath
by
5.7k points
0 votes
is this correct answer?
PLEASE HELP ASAP simplify the expressions below 1) 8 + (x-4 )2 2) - (x+3) + 3(-x -6) 3) 2(x-example-1
User Kenly
by
6.5k points